Women, Work, and the Economy : Macroeconomic Gains from Gender Equity - Elborgh-Woytek, Katrin (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
The proposed SDN discusses the specific macro-critical aspects of women's participation in the labor market and the constraints that prevent women from developing their full economic potential. Building on earlier Fund analysis, work undertaken by other organizations and academic research, the SDN presents possible policies to overcome these obstacles in different types of countries.